Hypercoagulable State in Patients with Takayasu’s Arteritis - Akazawa, Hiroshi; Ikeda, Uichi; Yamamoto, Keiji; Kuroda, Toshio; Shimada, Kazuyuki (Thrombosis and Haemostasis, 1996)
Thrombus formation is recognized pathologically in the affected arteries and is supposed to play a major role in the pathogenesis of Takayasu’s arteritis; however, hemostatic conditions in this disorder have not been elucidated fully. We determined plasma levels of molecular markers for platelet activity (platelet factor 4; PF4, β-throm-boglobulin; βTG), thrombotic status (thrombin-antithrombin III complex; TAT, fibrinopeptide A; FPA), fibrinolytic status (plasmin-β2-plasmin inhibitor complex; PIC, D-dimer), and endothelial injury (von Willebrand factor antigen; vWF:Ag, thrombomodulin; TM) in 30 patients with Takayasu’s arteritis and in 20 age-matched control subjects. Plasma levels of PF4, βTG, TAT, FPA and D-dimer, but not PIC, in patients with Takayasu’s arteritis were substantially higher than those in normal control subjects. The levels of these markers were not different between the active and inactive stages of the disease. Plasma levels of vWF:Ag in patients with Takayasu’s arteritis did not differ significantly from those in normal subjects, and plasma levels of TM were significantly lower than those in normal subjects. In patients with Takayasu’s arteritis, platelet and coagulation activities are significantly increased, leading to hypercoagulable state and thrombus formation, although there is little, if any, endothelial damage.